Application Of The Ne Bis In Idem Principle By Judges To Civil Cases - Alexander Wewo, Jeremia; Naatonis, Mathelda (Fakultas Hukum Universitas Mataram, 2023)
The purpose of the research is to analyze the judge's consideration so that case Number 268/Pdt.G/2021/PN.Kpg cannot be accepted because of ne bis in idem and to analyze the legal consequences of case Number 268/Pdt.G/2021/PN.Kpg which is declared ne bis in idem. Civil procedural law recognizes the principle of ne bis in idem which means that a case that has been decided by a judge and has permanent legal force cannot be resubmitted. The research method used is normative legal research which focuses on the law approach, concept approach, and case approach. The results of the study found that the basis for the consideration of declaring case Number 268/Pdt.G/2021 inadmissible due to ne bis in idem is that there are similarities in subjects, objects, legal relations, and courts and case Number 268/Pdt/2021/PN.Kpg has previously had a permanent legal decision and has a positive nature of the decision. The legal consequences of case Number 268/Pdt.G/2021/PN.Kpg which is declared ne bis in idem, namely first, the subject does not have legal standing to file a lawsuit against the same thing and the legal subject returns to its original state to obey the contents of the decision. Second, for the object, it cannot be re-filed in the same lawsuit and the legal object is legally valid. The suggestion given by the author is that there is a need for a basic understanding of ne bis in idem for parties who want or will file a lawsuit and there is a need to form a regulation that provides restrictions on cases that have ne bis in idem potential to not need to continue the examination until the subject matter.